Use of Soy-Based Formulas and Cow's Milk Allergy: Lights and Shadows - Verduci, Elvira; Di Profio, Elisabetta; Cerrato, Lucia; Nuzzi, Giulia; Riva, Luca; Vizzari, Giulia; D'Auria, Enza; Giannì, Maria Lorella; Zuccotti, Gianvincenzo; Peroni, Diego G. (Frontiers in Pediatrics, 2020)
Soybean (Glycine max) is a species of legume native to East Asia, used in childhood diet for over 2000 years in the East. Soy protein formulas have been available for almost a century. Nowadays, the increase in cow’s milk allergy and vegetarian dietary preferences are driving consumers towards cow’s milk alternatives. In this paper, we reviewed the nutritional composition of soy-based infant formula and discussed their possible use in pediatric age, mainly focusing on prevention and treatment of cow’s milk allergy. Protein quality is determined by digestibility and amino acid content. Purified or concentrated vegetable proteins (e.g. soy protein, gluten) have high digestibility (>95%), similar to those of animal ones. For some intact vegetable products (e.g. whole cereals and pulses), protein digestibility is lower (80-90%). Food processing and heat treatment also influence protein digestibility. Considering these data, we tried to evaluate the possible use of soybean and derivatives in pediatric age, including the nutritional composition of soy formulas and the clinical indications for their use. Moreover, since plant-based beverages are being perceived as healthy by consumers and their use is growing on the market, we recommend that soy drink should not be used as a substitute for infant formulas or cow’s milk in children younger than 24 months.